Aptidão de espécies florestais para a restauração ecológica em áreas de Floresta Estacional - Santos, Ivonir Piotrowski (Universidade Federal de São Carlos, 2016)
The classification of species by functional traits facilitates their selection for the restoration of ecological processes and their development in field conditions. In order to identify species with silvicultural suitability (survival and growth) in Deciduous Forest region in 2011, we performed an experiment in Sorocaba, SP, with high plant density (3 individuals / m²), diversity (142 species) and ecological functions ( biomass input , attractive to wildlife, fertilizing and soil cover). After 15 to 45 months we evaluated plant growth (heigh t - H, the height; diameter in soil level - DAC and survival - S) in 120 plots of 12.5 m². The species were classified as unsuitable (> 75% mortality at 15 months), sensitive to competition (> 75% mortality at 45 months), facilitative (> 50% mortality at 45 months) and stru ctur al (<50% mortality at 45 months). Based on the annual survival and periodic increment, grades were assigned to the structural species (high, medium, low and regular suitability ). From 77 selected species and 3945 individuals, only Calophyllum brasiliense (Cambess) was classified as unsuitable . From the remaining species, 8 (10.4%) were sensitive to competition and 10 (13.0%) were considered facilitative and the remainder were structur al . Among the sensitive species planted we observed ones with high frequency in restoration plantation , which may cause the occurrence of gaps over time favoring invasive reinfestation. It is recommended to avoid high density of sensitive species in larger spacing as well as increase the number of structural species in the initial formation of the planting
Forest speciessuitabilityfor ecological restoration in areas of Seasonal Forest
Keywords: Recuperação ecológica; Restoration ecology; Plantas florestais; Forest plants; Grupos ecológicos; Estabelecimento de espécies florestais; Espécies facilitadoras; Ecological groups; Establishment of forest species; Facilitative species; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA